Multiorgan paradoxical embolism in an elderly female with a patent foramen ovale: a case report - Anyfantakis, Dimitrios; Karona, Paraskevi; Kastanaki, Pagona; Kourakos, Athanasios; Kastanakis, Miltiades (Medicine and Pharmacy Reports, 2019)
Paradoxical embolism is an uncommon cause of arterial occlusion with a high mortality burden. Current evidence suggests that patent foramen ovale is the most important etiological factor of paradoxical embolism, by acting as a pathway for a thromboembolic material originating from the peripheral veins, passing through the lungs and entering the systemic circulation. Here we present a case of paradoxical embolism in the mesenteric and renal arteries associated with pulmonary embolism and deep vein thrombosis in an elderly woman with no predisposing risk factor. A diagnosis of paradoxical embolism was considered and the presence of a patent foramen ovale was consequently confirmed with a transesophageal echocardiography. Urgent thrombolysis saved the life of the patient. Paradoxical embolism represents an emergency and therefore prompt diagnosis and initiation of therapy may prevent adverse outcomes.